2004
DOI: 10.2746/0425164044877125
|View full text |Cite
|
Sign up to set email alerts
|

Equine laminitis: loss of hemidesmosomes in hoof secondary epidermal lamellae correlates to dose in an oligofructose induction model: an ultrastructural study

Abstract: Summary Reasons for performing study: Light microscopical studies show that the key lesion of laminitis is separation at the hoof lamellar dermal‐epidermal interface. More precise knowledge of the damage occurring in the lamellar basement membrane zone may result if laminitis affected tissue is examined with the transmission electron microscope. This could lead to better understanding of the pathogenesis of lesions and the means of treatment or prevention. Objectives: To investigate the ultrastructure of acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 11 publications
2
66
1
4
Order By: Relevance
“…Laminitis is considered as a systemic disease with clinical signs localized in the foot. Even where mitochondrial dysfunction has not been demonstrated in the foot, energy deficiency has been suggested as an explanation for the disruption of the hemidesmosomes leading to the failure of the dermal-epidermal interface [32].…”
Section: Discussionmentioning
confidence: 99%
“…Laminitis is considered as a systemic disease with clinical signs localized in the foot. Even where mitochondrial dysfunction has not been demonstrated in the foot, energy deficiency has been suggested as an explanation for the disruption of the hemidesmosomes leading to the failure of the dermal-epidermal interface [32].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies using an equine laminitis model performed euthanasia to obtain the lamellar samples (French et al 2004, Hurley et al 2006). This methodology is advantageous because numerous hoof lamellae, other tissues, and organ samples are available for each horse.…”
Section: Discussionmentioning
confidence: 99%
“…There are two distinct gelatinases of the MMPs family, MMP-2 and MMP-9, which are also found as proenzymes, produced by basal cells for physiologic control of hoof growth (FRENCH & POLLITT, 2004). It has been demonstrated that the concentration of these substances increases, substantially, 48 hours after laminitis induction through carbohydrate administration (KYAW-TANNER & POLLITT, 2004), and that MMP-9 seems to be better associated to inflammatory processes, since it is activated by proinflammatory cytokines and released by leukocytes, while MMP-2 is found in large quantities on normal tissues (KYAW-TANNER & POLLITT, 2004, LOFTUS et al, 2006.…”
Section: Introductionmentioning
confidence: 99%